AN ASSESSMENT OF CLIMATE CHANGE AND THE CONSEQUENCES OF MIGRATION IN AFRICA - Yahaya, Jibrin Ubale (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The issue of climate change has resulted to migration of large number of peoples from various African countries to different places in the world seeking for livelihood. The consequences of this action have blown up continues spread of migrant from Nigeria, Niger Republic, Chad and Cameroon as a victim of environmental related problems or insecurity, if proper care is not taking in the next 20 to 30 years coming the implication and dangers associated with migration can seriously damage the structure of functional Ecosystem operation in the African region and nature of governance conduct in many Africa countries. The paper will use secondary source of data to generate relevant information regarding to the research problem in the area of the study. The paper has two major findings, firstly, in Africa it has been observed that some our culture and human attitudes has some negative consequence to the healthy environment and secondly, most of the government policies in Africa has not address the problems of climate change that led to higher of number of migrations as a result of poverty, desertification, flooding and many other environmental problems.